DAMPAK PENJUALAN PAKAIAN BEKAS TERHADAP TINGKAT PENDAPATAN PEDAGANG DI PASAR SAMBU KOTA MEDAN DALAM PERSPEKTIF EKONOMI ISLAM - Isma Padillah; Kamilah Kamilah; Muhammad Lathief lhamy Nasution (Studia Economica : Jurnal Ekonomi Islam, 2021)
This study aims to determine the mpact of selling used clothes on the ncome level of mercants and what are the supporting and inhibiting factors n selling used clothes on the income levels of traders n the Medan city Sambu market and to determine the islamic economic view of the used clothes sale. The research uses descriptive qualitative method. Research location at Sambu market on Sutomo street, Medan city. Data collection techniques used are observation, interviews and documentation. The data analysis technique used s qualitation data analysis. From the results of the study, it can be concluded that the impact of selling used clothes on the income level of traders very influential on the economic level of traders, used clothing merchant businesses can make the economy of small communities, and help the middle and lower class to get branded clothes at very affordable prices. The inhibiting factors in the sale of used clothing to the income level of merchants are the Covid-19 pandemic, goverment bans and complaints from customers. And if viewed from an islamic economic perspective, buying and selling used clothes n the sambu market is permissible, because trading used clothes can help the needs and improve the economy even though the government with  this law prohibits the import of used clothes.